The Use of Recount Text by Implementing Pre-Questioning Technique to Improve the Students Reading Comprehension - Nur Rahmi Ratmeilia; Bahrun Amin; Erwin Akib (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this study was to determine whether the pre-questioning technique was effective in increasing students' understanding in reading recount text or not, and to find out how students' perceptions of the pre-questioning and answering technique applied by the teacher to their understanding of reading recount text.Â Â This study uses quantitative methods. This study used a pre-experimental design in which the pre-test, treatment, and post-test were carried out in class. The pre-test was conducted to determine the students' prior knowledge, while in the treatment process the students were taught recount text using the pre-question technique to improve their reading comprehension. Then a post-test was distributed to determine the progress or reading ability of students, this test was given after students were given treatment for four meetings through the pre-question technique.Â The findings showed that the application of pre-questions was effective in improving students' reading achievement, especially in reading recount texts, this was indicated by the students' post-test scores which were better than the pre-test, both on multiple choice questions and essay questions. In addition, student learning achievement has been shown to increase significantly. This is indicated by the pre-test and post-test interval scores. Students can also find the main idea and supporting details in the text.